Linking business strategy to management accounting: a study in Malaysian service organizations - Sofiah Md. Auzair; Rozita Amiruddin; Ainun Abdul Majid; Ruhanita Maelah (Penerbit Universiti Kebangsaan Malaysia, 2013)
Despite being economically and socially important to Malaysia, little has been done to study the innovations in the administration of service organizations to maintain the survival of such organizations in the globalization era. The purpose of this paper is to examine the use of strategic management accounting (SMA), as an administrative innovation, by the service organizations operating in Malaysia. The literature suggested that business strategy is an important factor affecting the use of SMA techniques and, as a result, the use of SMA will differ with different strategic priorities. The SMA techniques studied are costing, competitor accounting and customer accounting, while business strategy includes cost leadership and differentiation strategies. Survey questionnaires were administered to managers yielding 62 usable responses. Using ANOVA, the present study finds that service organizations pursuing differentiation strategies place higher emphasis on competitor and customer accounting compared to service organizations pursuing cost leadership strategies. The results also reveal that the highest emphasis on all SMA techniques is found in service organizations that place high emphasis on both strategies.The study provides evidence regarding practices that place high emphasis on strategic issues that lead to a high usage of innovative information systems.